Energy demand and factor substitution in Vietnam: Evidence from two recent enterprise surveys - Phu V. Le (Journal of Economic Structures, 2019)
Vietnam's economy is one of the most energy-intensive economies in the world, facilitated by long-standing government policies indirectly subsidizing energy prices through various state-owned enterprises in the energy sector. A consequence of this is that firms are using too much energy in production. This raises a crucial issue as to whether Vietnam can continue its development trajectory in the new era with rising energy prices and increased awareness of the use of fossil fuels and environmental pollution. In this context, understanding energy use patterns and firms' behaviors regarding cheap energy prices is critical to forming appropriate energy policies and management practices. Using large-scale firm-level data, we have found explicit evidence of firms' substitution of energy for capital inputs. This effect is present in both the short term and long term and in many energy-intensive industries. These results indicate that there is substantial benefit in appropriate pricing of primary energy and electricity, while also providing credit incentives for capital investment in more energy-efficient equipment. Reducing the rate of growth of energy demand, averaging approximately 10% annually, will have significant macroeconomic impacts. A quicker transition to less energy-intensive economic growth will also help to protect both the environment and public health.
Keywords: 330; Energy demand; KLEM; Elasticity of substitution; Translog production